Cosmos - Sagan, Carl, 1934- (New York : Random House, 1980)
Based on his 13-part television series, discusses science in a broad human context summarizing how science and civilization grew up together, considers the findings on life elsewhere, and the directions our science might take in the future.
Based on C. Sagan's 13-part television series.
Includes index.
Bibliography: p. [350]-355.
Young Adult.
Keywords: Astronomy -- Popular works; Astronomy